Three-Dimensional Bi(2)Te(3) Networks of Interconnected Nanowires: Synthesis and Optimization - Ruiz-Clavijo, Alejandra (Nanomaterials (Basel), 2018)
Self-standing Bi(2)Te(3) networks of interconnected nanowires were fabricated in three-dimensional porous anodic alumina templates (3D–AAO) with a porous structure spreading in all three spatial dimensions. Pulsed electrodeposition parameters were optimized to grow highly oriented Bi(2)Te(3) interconnected nanowires with stoichiometric composition inside those 3D–AAO templates. The nanowire networks were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), and Raman spectroscopy. The results are compared to those obtained in films and 1D nanowires grown under similar conditions. The crystalline structure and composition of the 3D Bi–Te nanowire network are finely tuned by controlling the applied voltage and the relaxation time off at zero current density during the deposition. With this fabrication method, and controlling the electrodeposition parameters, stoichiometric Bi(2)Te(3) networks of interconnected nanowires have been obtained, with a preferential orientation along [1 1 0], which makes them optimal candidates for out-of-plane thermoelectric applications. Moreover, the templates in which they are grown can be dissolved and the network of interconnected nanowires is self-standing without affecting its composition and orientation properties.